Sustainable Entrepreneurship Education (SSE) in Higher Education for Developing Students’ Green Entrepreneurial Mindset: A Scoping Review - Elvi Rahmi; Rani Sofya (Jurnal Ecogen, 2026)
Sustainable Entrepreneurship Education (SEE) plays a crucial role in preparing students to address sustainability challenges. However, existing research remains fragmented and focuses on specific aspects, thus failing to provide a comprehensive understanding of how various elements in higher education can collectively foster a green entrepreneurial mindset. This study aims to map and synthesize the literature on SEE in higher education through a scoping review approach. The review process followed the framework by Arksey and O’Malley as well as the PRISMA-ScR guidelines. A total of 51 articles were identified from the Scopus, ScienceDirect, and ERIC databases. Following a screening process and eligibility assessment based on inclusion and exclusion criteria, 12 articles were selected for analysis. The results of the study reveal four main dimensions of SEE: sustainability-based curriculum integration, experiential learning, institutional and ecosystem support, and technology-based entrepreneurship. These four dimensions contribute to shaping a green entrepreneurial mindset through increased sustainability awareness, critical thinking skills, entrepreneurial competencies, and sustainable entrepreneurial intent. This study offers a novel perspective by viewing SEE as an integrated educational system and provides practical implications for higher education institutions in designing sustainable entrepreneurship programs that support the achievement of the SDGs